2008
DOI: 10.1029/2007jc004537
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of the sea surface temperature in the Gulf of Trieste between January 2000 and December 2006

Abstract: [1] The variability of the sea surface temperature (SST) of the Gulf of Trieste (northeastern Adriatic Sea) is studied using satellite observations spanning 2000-2006. After interpolation and validation of the SST data with in situ observations near Trieste, the satellite data are used to compute various statistical estimates (7-year, yearly and monthly means and empirical orthogonal functions modes). The main results obtained are: 1. The SST in the Gulf of Trieste is mostly variable at the seasonal scale, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…S1). The Monfalcone site, located in the Gulf of Trieste, has a higher SST than typically expected for this latitude34.…”
Section: Resultsmentioning
confidence: 87%
“…S1). The Monfalcone site, located in the Gulf of Trieste, has a higher SST than typically expected for this latitude34.…”
Section: Resultsmentioning
confidence: 87%
“…According to other authors (Dailianis et al 2003;Koukouzika and Dimitriadis 2005;Ringwood et al 1998) neutral red retention times are influenced more by pollutants than natural factors, but the negative influence of high water temperatures (25 • C) in shortening the retention of dye within the lysosomes has been already demonstrated in other bivalve species (Hauton et al 1998). The anomalous and persistent high water temperatures (up to 28.5 • C) observed during the late spring-summer 2003 (Grbec et al 2007;Mauri et al 2008) might have seriously affected this parameter, which indeed showed low and homogeneous values throughout different sites. Lipofuscins were always significantly lower in June than in October in mussels ( Fig.…”
Section: Temporal Variability Of the Biological Responsesmentioning
confidence: 89%
“…BECKERS and RIXEN (2003), ALVERA-AZCÁRATE et al (2005), BECKERS et al (2006) andMAURI et al (2008) worked with SST in the Adriatic and Ligurian seas. DINEOF was applied to chlorophyll data in the northern Adriatic Sea by MAU-RI et al (2007).…”
Section: Review Of Basic Methodsmentioning
confidence: 99%
“…DINEOF was improved in ALVERA-AZCÁRATE et al (2005) by including an efficient EOF solver developed by TOUMAZOU and CRETAUX (2001). This addition allowed for the reconstruction of large data sets, and was applied to the Sea Surface Temperature (SST) of the Adriatic Sea.…”
Section: Review Of Basic Methodsmentioning
confidence: 99%